Agricultural and Aquaculture Wastes as Concrete Components: A Review - Wang, Wei; Wei, Wuyou; Gao, Shan; Chen, Guiming; Yuan, Jian; Li, Yu (Frontiers in Materials, 2021)
The application of agricultural and aquaculture waste in concrete greatly reduces the pressure on the ecological environment brought by traditional concrete production. The use of agricultural and aquaculture wastes as cement replacement, aggregate replacement and fiber reinforcement has showed great potential. Making full use of these wastes can not only alleviate the environmental pressure caused by mining, incineration, and landfill, but also help the development of sustainable circular green concrete. This paper provides an objective evaluation and summary of agricultural waste and aquaculture waste in green concrete. Agricultural waste is divided into natural plant fiber, agricultural waste ash and “comprehensive” waste according to useful function and alternative methods, such as sisal fiber, olive waste ash, and bamboo. Aquaculture waste mainly refers to some shells such as oyster shell. This paper analyzes the advantages and disadvantages of agricultural and aquaculture waste concrete applications that have been reported and shows how different agricultural and aquaculture wastes are made in concrete. In the end, the selection of appropriate treatment methods and usage scenarios is extremely important for agricultural and aquaculture waste concrete, it can determine whether the waste concrete has reliable performance. This paper will lay a solid foundation for the progress of waste concrete and provide reliable help for the development of environmental protection concrete.